(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In the development of naturalistic knowledge about the nature of the territory of Uzbekistan, the construction of new cities, the emergence of irrigation facilities, the development of handicrafts based on the information written down by Arab and Iranian tourists such as ibn Hudodbek, ibn Rustad, al-Masudi, Istakhri, Yaqut, ibn Batuta, who lived in the Middle Ages The scope of human influence on nature has expanded, and knowledge about the living environment, natural elements, climate, surface structure, water, soil vegetation has been studied. The dams, canals, ponds, mined remains of mines, ruins of old cities such as Afrosiyob, built in the territory of Uzbekistan, are full proof.